Wearing God : clothing, laughter, fire, and other overlooked ways of meeting God - Winner, Lauren F. (New York : HarperOne, an imprint of HarperCollins Publishers, 2015)
"There are hundreds of metaphors for God, but the church only uses a few familiar images: creator, judge, savior, father. In [this book], Lauren Winner gathers a number of lesser-known tropes, reflecting on how they work biblically and culturally, and reveals how they can deepen our spiritual lives"--Amazon.com.
The God who runs after your friendship -- A short note on gender and language for God -- Clothing -- Smell -- Bread and vine -- Laboring woman -- Laughter -- Flame -- In this poverty of expression, thou findest that He is all -- A short note from the women's prison -- A bookshelf to quicken your scriptural imagination.
Includes bibliographical references.
Keywords: Image of God; Spirituality -- Christianity; Spiritual life -- Christianity; Christian women -- Religious life